Victim Support and the Welfare State - Gallo, Carina (Taylor & Francis, 2019)
This book provides a rich analysis of the history of Swedish victim support. With the majority of research on victim support centering on the Anglosphere, this book offers a unique case study for considering the role of the victim in the criminal justice system. While Sweden has enacted many laws to support victims, and victim assistance programs have grown rapidly, welfare policy has become more restrictive and crime policy, to some degree, more punitive. Drawing on archival material and interviews with key representatives for the Swedish Association for Victim Support (BOJ), this book examines what role the victim movement has played in a changing welfare state. It argues that BOJ filled a function in the decentralization and privatization of the Swedish welfare state and explores distinctive features of the Swedish victim movement and the form it has taken, as compared to that in other countries.This book will be of interest to scholars and students of criminology, sociology, social policy, civil society studies, and social work, and those engaged in studies of victims and victimology.